Parkinson's Disease and Bipolar Disorder: a case report and narrative review. (1st June 2022) - Andreu Gracia, H.; Ilzarbe, L.; Marco Estrada, O.; Bueno Sanya, L.; De Juan Viladegut, O.; Olivier Mayorga, L.; Pintor, L.; Valldeoriola, F.; Grande, I.
Abstract : Introduction: Bipolar disorder (BD) is considered a risk factor for developing Parkinson's Disease (PD) because of an altered dopamine activity in both entities. Comorbidity may delay diagnosis and difficult therapeutic management. Objectives: To describe the case of a patient with both BD and PD and to determine the appropriate diagnostic and therapeutic approach for patients presenting both entities. Methods: We present the case of a 58-year-old woman attended in our neurology unit due to the initial presence of visual hallucinations as a core symptom. Results: Psychotic symptoms as hallucinations and off-times, frequently observed in PD, may be misdiagnosed with a worsening of depressive polarity of BD. Thus, overlap between symptoms may lead to a challenging differential diagnosis. Moreover, there is no consensus about the therapeutic management of the comorbidity, due to the bidirectional worsening of symptoms when treatment is adjusted. In our case, a diagnosis of dopaminergic psychosis was made so antipsychotic treatment with quetiapine 50 mg/d was initiated. A worsening of symptoms was observed, presenting the patient a stuporous status, mutism and generalized rigidity. Neuroimaging and lumbar puncture were performed showing no alterations; electroencephalogram showed diffuse slowing. Final diagnosis was an off-episode of PD and a multifactorial encephalopathy resulting in visual hallucinations. Conclusions: Coexistence of PD and BD may lead to a diagnostic and therapeutic delay and therefore a worse prognosis. Although these diseases are well-known, it is still challenging to manage patients presenting both entities. Further research is needed to clarify the proper diagnostic and therapeutic approach for these patients. Disclosure: No significant relationships.